BENTUK CAMPUR KODE DAN ALIH KODE DALAM CATATAN NAJWA BERSAMA MAUDY AYUNDA PADA CHANNEL YOUTUBE NARASI NAJWA SHIHAB - Meti Fitrotunnisa Karina; Cintya Nurika Irma; Deni Permadi (Universitas Sebelas Maret, 2021)
The research aims to determine and describe the use of language experienced by Naswa Shihab and Maudy Ayunda on the youtube channel Narasi Naswa Shihab which includes code mixed and code switching. The research was conducted using descriptive qualitative methods, namely the observation and note data collection technique that pay attention to the data on aspects of deep understanding of a problem. The research data is the utterances of Najwa Shihab and Maudy Ayunda in “Najwa Notes With Maudy Ayunda” on the youtube channel narration of Najwa Shihab. Based on the results of the research and analysis carried out on the use of the Najwa Shihab language on the youtube channel there were events of code mixing and code switching. Theserelated conclusion include: 1) A form of code mixing in the use Najwa Shihab and Maudy Ayunda language usage speeches on social media, especially youtube Najwa Shihab, 2) The form of code switching for the use of the language Najwa Shihab and Maudy Ayunda on social media, especially youtube Najwa Shihab.